HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN KECEPATAN LARI 40 METER SISWA KELAS V SDN 001 LANGGAM KABUPATEN PELALAWAN - Syusilaiman '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s of student in grade V of 001 Langgam Primary School, research found some student have not mastered the basic techniques of sprinting 40 meters with good, like start or finish, the students feel tired while sprinting. The purpose of this research is to see how much the correlations of exsplosive power leg muscles with 40 meter run result of student in grade V of 001 langgam primary school of pelalawan regency. Population in this research were all students in grade V of 001 Langgam Primary School who were 26 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 26 people. Research instrument used vertical jump test and 40 meters running speed test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is corelations of explosive power leg muscle with the 40 meter running speed of male student which shows correlation rhitung =0,631> rtabel =0,602 and there is no corelations of explosive power leg muscle with the 40 meter running speed of female student which shows correlation rhitung =0,006> rtabel =0,553Key word : explosive power leg muscles, 40 yard running